Analisis Proksimat dan Fisik Rolade Ikan Nila Merah - Junianto; Amanda Puspa Danella (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Roulade is a diversified product of processed meat, including fish, which is currently on the rise. It is important to pay attention to the quality of roulade products so that this product continues to exist. This research aims to determine the proximate value (protein and fat content) and physical properties of red tilapia roulade with the addition of carrageenan flour. This research was carried out at the Chemical Applications and Services Laboratory, Building D, Faculty of Mathematics and Natural Sciences, Padjadjaran University, and the Food Technology Laboratory, Faculty of Agricultural Industrial Technology, Padjadjaran University. The research method used was the testing of roulade samples in the form of fat and protein content tests, and physical tests in the form of folding tests and texture analysers. Proximate analysis of red tilapia roulade with the addition of 1% carrageenan flour, including protein and fat content, meets SNI 8504 - 201 standards. The protein and fat content of this red tilapia roll is 14.64% and 11.19% respectively. The physical properties of the red tilapia roll, which include hardness, springiness, cohesiveness, gumminess, chewiness and elasticity, are 2,991.4930 g force, 4.3430%, 0.9130%, 2,731.4853 g force, 12,970.4240 g force and 0.8710% respectively. The folding test shows the springiness criteria with a rating of A.